2014
DOI: 10.1021/la502287m
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Various Types of Inverse Micelles in Nonpolar Liquids Using Transient Current Measurements

Abstract: Transient current measurements are used to characterize a wide variety of charge carriers in nonpolar liquids. The transient current method allows us to obtain both the concentration and mobility of charge carriers and therefore also the hydrodynamic radius using Stokes' law. In this article, five different surfactants in dodecane are investigated: OLOA11K, Solsperse13940, Span80, Span85, and AOT. We show that different types of currents are observed depending on the size of the inverse micelles. For large inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 34 publications
4
49
0
Order By: Relevance
“…In our previous study we found a mobility of 3.6 × 10 −9 m 2 V −1 s −1 , and a concentration of 6.0 × 10 18 m −3 per weight percent for charged AOT inverse micelles. 40 The steady state currents for devices with Al 2 O 3 coated electrodes with thicknesses of 10, 27, and 57 μm are shown in Figures 3(a−c) For example, in Figure 3a the measurement in a 10 μm device at the lowest concentration of ϕ m = 0.0003 shows a linearly increasing current up to the saturation voltage of 1 V. Above this saturation voltage the current is not exactly constant but is slowly increasing less than proportionally with the voltage. Because of this it makes sense to define the saturation voltage as the voltage at which a significant deviation from the linear increase is observed.…”
Section: Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study we found a mobility of 3.6 × 10 −9 m 2 V −1 s −1 , and a concentration of 6.0 × 10 18 m −3 per weight percent for charged AOT inverse micelles. 40 The steady state currents for devices with Al 2 O 3 coated electrodes with thicknesses of 10, 27, and 57 μm are shown in Figures 3(a−c) For example, in Figure 3a the measurement in a 10 μm device at the lowest concentration of ϕ m = 0.0003 shows a linearly increasing current up to the saturation voltage of 1 V. Above this saturation voltage the current is not exactly constant but is slowly increasing less than proportionally with the voltage. Because of this it makes sense to define the saturation voltage as the voltage at which a significant deviation from the linear increase is observed.…”
Section: Experimental Datamentioning
confidence: 99%
“…For the surfactant OLOA1200 38 and in more detail for OLOA 11K 40 this is achieved by measuring generation-limited quasi steady-state currents. These generation-limited currents are due to bulk disproportionation since they scale with the square of the surfactant concentration and scale proportionally with the liquid volume.…”
Section: Introductionmentioning
confidence: 99%
“…The surfactants OLOA 11K (r ≈ 5.5 nm 11,25,26 ) and Span 80 (r ≈ 4 nm 26 ) are non-ionic while Solsperse 13940 (r ≈ 8 nm 26 ) is an ionic surfactant. The second category includes surfactant systems such as ionic sodium dioctylsulfosuccinate or Aerosol OT (AOT) (r ≈ 1.6 nm 2,3,26 ) and non-ionic sorbitan trioleate or Span 85 (r ≈ 3 nm 26,27 ), in which the generation rate of CIMs is much higher than their transportation rate to the opposite polarity electrode on application of an electric field. Therefore, in these surfactant systems, the concentration of CIMs in the bulk always remains approximately equal to the equilibrium concentration 24,26 .…”
Section: Introductionmentioning
confidence: 99%
“…The second category includes surfactant systems such as ionic sodium dioctylsulfosuccinate or Aerosol OT (AOT) (r ≈ 1.6 nm 2,3,26 ) and non-ionic sorbitan trioleate or Span 85 (r ≈ 3 nm 26,27 ), in which the generation rate of CIMs is much higher than their transportation rate to the opposite polarity electrode on application of an electric field. Therefore, in these surfactant systems, the concentration of CIMs in the bulk always remains approximately equal to the equilibrium concentration 24,26 . Also, the behavior at interfaces of each category of CIMs is different, the CIMs of the first category surfactant systems end up in a diffuse double layer 28 while that of the second category CIMs form interface layers 24 at the electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…24,26,39 Measuring transient currents in response to a voltage step is a well-known sensitive technique for studying the surfactantmediated charging and charge dynamics in nonpolar systems. 25,39,40 In the case of surfactant systems such as OLOA 11K, Span 80, and Solsperse 13940, when the voltage is reversed abruptly (V 0 → −V 1 ) after a sufficiently long polarizing voltage step (0 → V 0, V 0 > 1 V, t 0 > 100 s), a second peak is observed in the transient current, which is not explained by drift and diffusion. 29 Measurements have shown that the integral of this peak increases with increasing duration of the polarizing voltage step, with increasing device thickness, and with increasing mass fraction of surfactant in the mixture.…”
Section: ■ Introductionmentioning
confidence: 99%